The development of child protection law and policy - Walsh, Kieran. (London)
1 online resource.
Keywords: This book examines how child protection law has been shaped by the transition to late modernity and how it copes with the ever-changing concept of risk. The book traces the evolution of the contemporary child protection system through historical changes, assessing the factors that have influenced the development of legal responses to abuse over a 130-year period. It does so by focussing on the Republic of Ireland where child protection has become emblematic of wider social change. The work draws on a wide range of primary and secondary sources including legislation, case law and official and media reports of child protection inquiries. It also utilises insights developed through an extensive examination of parliamentary debates on child protection matters. These materials are assessed through the lens of critical discourse analysis to explore the relationship between law, social policy and social theory as they effect child protection. While the book utilises primarily Irish sources, this multidisciplinary approach ensures the argument has international applicability. The book will be a valuable resource for all those with an interest in the development of child protection law.